Analisis Diagnosis Kesulitan Belajar Siswa sebagai Dasar Program Remedial dan Pengayaan - Rini Irenci Toto; Priska Apilia Leo (Indo Publishing, 2026)
Learning difficulties are a common problem encountered in formal education processes, particularly at the primary and secondary school levels. This phenomenon significantly impacts students’ academic achievement and potentially hinders the optimal development of their potential. This study aims to examine various concepts and classifications of learning difficulties experienced by students based on comprehensive theoretical reviews, analyze various instruments and diagnostic procedures for learning difficulties that teachers can implement in classroom practice; and formulate a model of remedial and enrichment programs derived from diagnostic results as effective and equitable intervention strategies. This research uses a descriptive qualitative approach with a systematic literature review method of more than twenty scientific sources published in the 2019–2025 period. The findings indicate that systematically and data-based diagnosis of learning difficulties is a primary prerequisite for the success of remedial and enrichment programs. Teachers who can accurately identify the type, level, and causal factors of learning difficulties will be more effective in designing learning interventions appropriate to individual students’ needs. Effective remedial programs must include modifications of the learning approach, structured scaffolding, and continuous formative evaluation. Enrichment programs, meanwhile, need to be creatively designed to optimally promote student potential development.